Framing borders in literature and other media - Wolf, Werner, 1955-; Bernhart, Walter (Rodopi, 2006)
This book is both a contribution to an interdisciplinary study of literature and other media and a pioneering application of cognitive and frame-theoretical approaches to these fields. In the temporal media a privileged place for the coding of cognitive frames are the beginnings while in spatial media physical borders take over many framing functions. This volume investigates forms and functions of such framing spaces from a transmedial perspective by juxtaposing and comparing the framing potential of individual media and works. After an introductory theoretical essay, which aims to clarify ba.
Sixteen of the eighteen case studies are "revised contributions to a conference on 'Framing in Literature and Other Media' held in Graz in June 2004"--Page 11.
Keywords: Arts -- Psychological aspects -- Congresses.; Borders, Ornamental (Decorative arts) -- Congresses.; Boundaries in literature -- Congresses.; Frame-stories -- Congresses.; Motion pictures -- Aesthetics -- Congresses.; Music -- Philosophy and aesthetics -- Congresses.; Bordures (Arts décoratifs) -- Congrès.; Frontières dans la littérature -- Congrès.; Récits enchâssés -- Congrès.; Cinéma -- Esthétique -- Congrès.; Musique -- Philosophie et esthétique -- Congrès.; Arts -- Aspect psychologique -- Congrès.; ART -- Reference.; ART -- Performance.; Arts -- Psychological aspects; Borders, Ornamental (Decorative arts); Boundaries in literature; Frame-stories; Motion pictures -- Aesthetics; Music -- Philosophy and aesthetics; Conference papers and proceedings